PENGARUH DISIPLIN KERJA DAN KESEHATAN KESELAMATAN KERJA (K3) TERHADAP KINERJA KARYAWAN PT. TANUA INDEPENDENT MAJU SEJAHTERA - Pratama Marbun, Midian; Waty, Lenita; M. Hutabarat, Francis (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This research aims to evaluate the impact of work discipline and work safety (K3) on employee performance, both partially and simultaneously. The population studied was all employees of PT. Tanua Independent Maju Sejahtera, numbering 54 people. The research results show that work discipline partially influences work performance, as well as work safety (K3) which also has a partial impact on performance. Apart from that, these two variables simultaneously influence employee performance.